New inorganic scintillators on the basis of LBO glass for neutron registration - Zadneprovski, B.I.; Eremin, N.V.; Paskhalov, A.A. (Functional Materials, 2005)
Undoped lithium borate glasses and those doped with Сu, Се, Sm, Eu, Тb, Тm, Yb have been synthesized; the optical and luminescence properties thereof have been determined as well as some scintillation characteristics at registration of neutrons (Eₙ ≤ 10 MeV) and of the ⁶⁰Со у radiation. The lithium borate glassy scintillators have been established in experiment to have a high sensitivity to neutrons and to be suitable to record selectively neutrons in mixed radiation fields. The results obtained evidence that such scintillators can be an alternative of promise to the known neutron detectors based on gases, liquids, plastics, and crystals. Синтезированы сцинтилляционные литий-боратные стёкла чистые и активированные примесями Сu, Се, Sm, Eu, Тb, Тm, Yb. Определены их оптические и люминесцентные свойства, а также некоторые сцинтилляционные характеристики при регистрации нейтронов с энергией до 10 МэВ и гамма-излучения ⁶⁰Со. Экспериментально установлено, что литий-боратные стеклообразные сцинтилляторы имеют высокую чувствительность к нейтронам и эффективны для их селективной регистрации в полях смешанных излучений. Полученные результаты показывают, что сцинтилляторы этого типа могут являться перспективной альтернативой известным детекторам нейтронов на основе газов, жидкостей, пластмасс и кристаллов. Синтезовано чистi та легованi активуючими домiшками Сu, Се, Sm, Eu, Тb, Тm, Yb лiтiй-боратнi стекла та визначено їхнi оптичнi та люмiнесцентнi властивостi та деякi сцинтиляцiйнi характеристики при реестрації нейтронiв з енергiєю до 10 МеВ та гамма-промiння ⁶⁰Со. Експериментально встановлено, що лiтiй-боратнi склоподiбнi сцинтилятори мають високу чутливiсть до нейтронiв i можуть бути застосованi для селективної реєстрації нейтронiв у полях змiшаних випромiнювань. Одержанi результати свiдчать, що сцинтилятори цього типу можуть бути перспективною альтернативою вiдомих детекторiв нейтронiв на основi газiв, рiдин, пластмас та кристалiв.